Neuronal IL‐4Rα modulates neuronal apoptosis and cell viability during the acute phases of cerebral ischemia. (24th May 2018) - Lee, Han Kyu; Koh, Sehwon; Lo, Donald C.; Marchuk, Douglas A.
Abstract : Ischemic stroke caused by an embolus or local thrombosis results in neural tissue damage (an infarct) in the territory of the occluded cerebral artery. Decades of studies have increased our understanding of the molecular events during cerebral infarction; however, translation of these discoveries to druggable targets for ischemic stroke treatment has been largely disappointing. Interleukin‐4 (IL‐4) is a multifunctional cytokine that exerts its cellular activities via the interleukin‐4 receptor α (IL‐4Rα). This cytokine receptor complex is associated with diverse immune and inflammatory responses. Recent studies have suggested a role of the cytokine IL‐4 in long‐term ischemic stroke recovery, involving immune cell activity. In contrast, the role of the receptor, IL‐4Rα especially in the acute phase of infarction is unclear. In this study, we determined that IL‐4Rα is expressed on neurons and that during the early phases of cerebral infarction (24 h) levels of this receptor are increased to regulate cellular apoptosis factors through activation of STAT6. In this context, we show a neuroprotective role for IL‐4Rα in an in vivo surgical model of cerebral ischemia and in ex vivo brain slice explants, using both genetic knockout of this receptor and RNAi‐mediated gene knockdown. IL‐4Rα may therefore represent a novel target and pathway for therapeutic development in ischemic stroke. Abstract : Ischemic stroke causes brain tissue damage (infarction) leading to disability and/or death. Despite decades of research into the molecular events during cerebral infarction, treatment options are limited and alternative strategies for ischemic stroke treatment are urgently needed. Marchuk et al . have determined that the interleukin‐4 receptor α (IL‐4Rα) is expressed on neurons, with levels increasing dramatically in the early phase (24 h) of cerebral infarction. IL‐4Rα induces apoptosis via activation of STAT6 signaling. A neuroprotective role for IL‐4Rα was shown in an in vivo surgical model of cerebral ischemia and in ex vivo brain slice explants, using both genetic knockout and RNAi‐mediated gene knockdown. Together, these results suggest a novel target and pathway for therapeutic development in ischemic stroke.